Fairness and the Unselfish Demand for Redistribution by Taxpayers and Welfare Recipients. - Sabatini, Fabio; Ventura, Marco; Yamamura, Eiji; Zamparelli, Luca (Southern Economic Journal, 2020)
We theoretically illustrate how the aversion to unfairness triggers an unselfish though rational demand for redistribution. This leads the well‐off to demand positive tax rates and the "poor" to reject extreme progressivity. We prove that the "rich" and the "poor" adjust their demand for redistribution in opposite ways when their sensitivity to fairness increases: while agents with above average expected income raise their demand for redistribution, agents with below average income lower it. We then provide empirical evidence of these behaviors using a nationally representative survey from Italy. The estimates confirm that a stronger aversion to unfair distributive outcomes is associated with a higher support for redistribution by individuals with high income and to a lower demand for redistribution by those with low income.